2017
DOI: 10.1007/s00246-017-1593-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biomarkers of Myocardial Remodeling and Coronary Dysfunction in Early Stages of Hypertrophic Cardiomyopathy in the Young

Abstract: Hypertrophic cardiomyopathy (HCM) remains the leading cause of sudden cardiac death in the young. Early markers for HCM are important to identify individuals at risk. The aim of this study was to investigate novel serum biomarkers reflecting myocardial remodeling, microfibrosis, and vascular endotheliopathy in the early stages of familial HCM in young patients. Twenty-three HCM patients, 16 HCM-risk individuals, and 66 controls (median 15 years) underwent echocardiography and serum analysis for cathepsin S, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 41 publications
1
28
0
1
Order By: Relevance
“…MMP-9 has previously shown to be associated with LV wall thickness and decreased LVEF in symptomatic HCM (7,8). In patients with myocardial infarction, MMP-9 correlated with LV dysfunction and remodeling, indicating a pivotal role in cardiac fibrosis (9).…”
Section: Discussionmentioning
confidence: 95%
“…MMP-9 has previously shown to be associated with LV wall thickness and decreased LVEF in symptomatic HCM (7,8). In patients with myocardial infarction, MMP-9 correlated with LV dysfunction and remodeling, indicating a pivotal role in cardiac fibrosis (9).…”
Section: Discussionmentioning
confidence: 95%
“…Fernandez-Sola et al, demonstrated cardiac myostatin upregulation in hearts with cardiomyopathy of hypertensive, alcoholic, valve and coronary origins [ 172 ]. Furthermore, Fernlund et al, discovered no difference regarding circulating myostatin concentration in the serum of young patients with hypertrophic cardiomyopathy in comparison to healthy controls, despite lower myostatin levels in patients at risk of this disorder, which indicates a potential role of myostatin in the development of hypertrophic cardiomyopathy [ 173 ].…”
Section: Factors Affecting Myostatin Concentrationmentioning
confidence: 99%
“…Given these facts, it is of interest to seek evidence for prehypertrophic processes affecting fibrotic and vascular remodeling. Current evidence in humans indicates an early remodeling process with increases in circulating cathepsin S and endostatin correlating with diastolic dysfunction [34]. Others have shown increases in collagen synthesis detected by increased PICP, an unusual finding in a pressure-overloaded system without significant hypertrophy [54].…”
Section: Microcirculatory Alterations and Prehypertrophymentioning
confidence: 99%